2009
DOI: 10.1002/cyto.b.20482
|View full text |Cite
|
Sign up to set email alerts
|

Sample stability and variability of B‐cell subsets in blood from healthy subjects and patients with systemic lupus erythematosus

Abstract: Objective: Characterization of peripheral leukocytes is an important aspect of monitoring the effect of immunotherapeutic interventions in systemic lupus erythematosus (SLE). We analyzed cell surface markers commonly used to assess patients with SLE, focusing on the effect of holding blood prior to processing/analysis and the relative reliability of the measurements that were conducted.Methods: Healthy volunteers (HV; n 5 20) and patients with SLE (n 5 42) were studied. Whole blood was collected for flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…In the case of small populations, which are given similar weight in standardized lymphocyte fractions, small variations in staining intensity can lead to large VARIABILITY AND CLUSTERING OF LYMPHOCYTE SUBSETS relative changes. Others have also found that variability was proportionally greater for measurements of numerically smaller subsets of lymphocytes (5,6,10,12). In the case of absolute cell counts, additional sources of variation including analytical (e.g., the complete blood count (13), and the use of a dual platform method, as discussed above) and biological [e.g., diurnal shifts (14)], contribute to increased inter-and intraindividual variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of small populations, which are given similar weight in standardized lymphocyte fractions, small variations in staining intensity can lead to large VARIABILITY AND CLUSTERING OF LYMPHOCYTE SUBSETS relative changes. Others have also found that variability was proportionally greater for measurements of numerically smaller subsets of lymphocytes (5,6,10,12). In the case of absolute cell counts, additional sources of variation including analytical (e.g., the complete blood count (13), and the use of a dual platform method, as discussed above) and biological [e.g., diurnal shifts (14)], contribute to increased inter-and intraindividual variability.…”
Section: Discussionmentioning
confidence: 99%
“…These reasons include preanalytical variables such as the source, condition, and manner of preservation of the sample, the time of day that the blood was drawn, subject age, disease state, and medications (5)(6)(7)(8). Analytical variables include instrumentation, instrument settings, the types and quantities of antibody-fluorophore conjugates, and the manner in which lymphocyte subsets are defined and electronically gated (5,9,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, DN memory B cells are also included in Figure 3A. This system is still routinely used to monitor changes in peripheral B cell composition in patients with SLE treated with investigational agents (Belouski et al, 2010 , and CD77 expression in addition to IgD. This resulted in a classification scheme whereby "mature B cells" were binned into categories Bm1 through Bm5 ( Figure 3B) (Pascual et al, 1994 (Bohnhorst et al, 2001).…”
Section: Antigenic Pillars Of B Cell Biology -Classification and Caveatsmentioning
confidence: 99%
“…However, a cell stabilization formula that truly extends the stability of blood without impacting resolution of dim markers has yet to be brought forward. Peripheral (whole) blood is the specimen of choice in our laboratory because the composition of cells in the unseparated and unfrozen state is most likely to resemble the in vivo state of the blood donor (Belouski et al, 2010). Peripheral blood analysis also has the advantage that the cells are exposed to the biologic matrix throughout the assay.…”
Section: Specimen Stabilitymentioning
confidence: 99%